MENELAAH SIFAT-SIFAT PRODUK HASIL DESTILASI KERING LIMA JENIS KAYU ASAL KALIMANTAN TIMUR - Gustan Pari; Dadang Setiawan; Mahpudin Mahpudin (Jurnal Penelitian Hasil Hutan, 2002)
Dry-distillation trials of five wood species from East Kalimantan were conducted at the forest products laboratories. Bogor. and the characteristics of the products (i.e. charcoal, tar and distillate fractions) were assessed to explore their possible uses as a fuel (the source of energy), activated charcoal. carbon-based fibers, metallurgy (smelter), disinfectant, and fertilizer. The distillation was performed in an electrically heated retort. The wood species were consecutively Kayu Arang (Diospyros macrophylla), Nyaling (Mastixia trichotama). Penjalin (Drypetes). Lansat Hutan (Lansium) dan Kayu Gading (Koilodepes sp.). Before conducting the experiment, these wood species were each examined for their specific gravity and calorific values. These species showed variation in their specific gravity (0.51 - 0.93) and calorific values (4465 - 4606 cal/g). Further, the products of distillation revealed some variation in their yielas, i.e. 27.55 - 33. 75 % (for charcoal), 6.53 - 12.89 % (tar). and 47.44 - 71.92 % (pyrolignous liquor). As the charcoal, its moisture content ranged from 0.89 - 1.73 %, ash content from 3.04 - 3.40 %. volatile matter from 19.15 - 20.65 %, fixed carbon from 76.05 - 77.81 %. and charcoal calorific value from 6802 - 7086 cal/g Based on the calorific value. volatile matter, and ash content of their resulting charcoal, the five species tested were all suitable as raw materials for the manufacture of metallurgy charcoal and activated charcoal.